A Brief Review On: Kidney Stone - Ansari, Ashiya; Singh, S. P.; Khinchi, M. P.; Shama, Parveen; Mahaver, Megha (Asian Journal of Pharmaceutical Research and Development, 2017)
The kidneys are two bean-shaped organs that are roughly four inches in length. They are located towards the back of the abdomen (stomach) on either side of the spine. The kidneys remove waste products from the blood and transfer them into the ureter, along with excess fluids. The ureter is the tube that attaches each kidney to the bladder. From there, the waste products and excess fluid are disposed of as urine. There are four types of kidney stone. Calcium Stone, Uric Acid Stone, Struvite Stone, Cystine Stone, Kidney stone. Kidney stones typically form in the kidney and leave the body in the urine stream. A small stone may pass without causing symptoms. A stone may also result in blood in the urine, vomiting, or painful urination. Pathophysiology are complete in three steps: Hypocitraturia, Supersaturation of urine, Inhibitors of stone formation. In these article mention the symptoms of kidney ston: Severe pain in the side and back, below the ribs, Pain on urination, Pink, red or brown urine. Way of the passes of kidney stone such as: Drinking more fluids, Lemon juice, olive oil & Avoiding alcohol. Diagnosis of kidney stones is made on the basis of information obtained from the history, physical examination, urinalysis, and radiographic studies. Clinical diagnosis is usually made on the basis of the location and severity of the pain, which is typically colicky in nature (comes and goes in spasmodic waves). measures depend on the type of stones. In those with calcium stones, drinking lots of fluids, thiazide diuretics and citrate are effective as is allopurinol in those with high uric acid levels in the blood or urine.